Glutamate dehydrogenase 1-dependent α-ketoglutarate promotes hepatitis B virus transcription by modulating histone methylations on the covalently closed circular DNA minichromosome - Sheng-Tao Cheng; Wei-Xian Chen; Hai-Jun Deng; Xin He; Hui Zhang; Ming Tan; Hai-Bo Yu; Zhen-Zhen Zhang; Ji-Hua Ren; Min-Li Yang; Da-Peng Zhang; Zhi-Hong Li; et al. (Clinical and Molecular Hepatology, 2025)
Background/Aims Hepatitis B virus (HBV) hijacks host cell metabolism, especially host glutamine metabolism, to support its replication. Glutamate dehydrogenase 1 (GDH1), a mitochondrial enzyme crucial for glutamine metabolism, can interact with histone demethylases to regulate gene expression through histone methylation. However, the mechanisms underlying GDH1-mediated glutamine metabolism reprogramming and the roles of key metabolites during HBV infection remain unclear. Methods Transcriptomic and metabolomic analyses of HBV-infected cell were performed. Both HBV-infected cells and humanized liver chimeric mice were used to elucidate the effect of glutamine metabolism on HBV. Results HBV infection leads to the abnormal activation of glutamine metabolism, including upregulation of key enzymes and metabolites involved in glutamine metabolism. The viral core protein (HBc) mediates the translocation of GDH1 into the nucleus, where GDH1 activates covalently closed circular DNA (cccDNA) transcription by converting glutamate to α-ketoglutarate (αKG). Mechanistically, the promoting effect of GDH1-derived αKG on cccDNA transcription is independent of its conventional role. Rather, αKG directly interacts with the lysine-specific demethylase KDM4A and enhances KDM4A demethylase activity to regulate αKG-dependent histone demethylation, controlling cccDNA transcription. Conclusions Our findings highlight the importance of glutamine metabolism in HBV transcription and suggest that glutamine deprivation is a potential strategy for silencing cccDNA transcription.